PTH-061 The Management Of Acute Upper Gastrointestinal Bleeding In Paediatric Practice: A National Survey. (9th June 2014) - Henderson, P; Hansen, R; Russell, RK; McGrogan, P
Abstract : Introduction: Acute upper gastrointestinal (GI) haemorrhage is rare in paediatric practice but continues to cause significant morbidity and mortality. Guidelines for the management of GI bleeding in children exist but their evidence base is limited and their implementation in the UK is unknown. We aimed to determine the provision for paediatric upper GI bleeding in the UK with regard to access to services and management using a national survey. Methods: In August 2013 an electronic survey containing 20 questions was sent to the 18 RCPCH-approved National GRID paediatric gastroenterology training centres who also act as regional referral centres. The questionnaire was completed online by either the departmental clinical or endoscopy lead and results collated by the study centre. Descriptive statistics were used to present results. Results: Sixteen centres responded, representing the experience of 65.6 whole-time equivalent (WTE) consultant paediatric gastroenterologists. Half of centres provided out-of-hours cover for GI emergencies in their region, with surgeons providing the majority (69%) of out-of-hours support, often in conjunction with GI specialists (44%), for acute upper GI bleeds. 11/16 centres dealt with <20 endoscopies for upper GI bleeding annually with 3 centres dealing with >40/year. 63% of tertiary centres had a GI haemorrhage protocol available in electronic format (online/shared-drive), but 53% were not aware of a similar protocol in their respective DGHs; only 31% of centres provided 'at-risk' patients with emergency cards/advice. 88% of centres had access to interventional radiology in-hours and 63% out-of-hours. The injection of vasoconstrictors/sclerosants/thrombotic agents and endoclips were available in all but one centre, however only 19% of centres (with between 3–4.6 WTE consultants) stated that all their consultants were competent in managing upper GI bleeds, with the same percentage stating that no consultant was competent in management; very few procedures were carried out by trainees. Only half of centres were undertaking regular case review of paediatric bleeding cases. All respondents were keen to be involved in a detailed review of UK practice. Conclusion: Our national survey of tertiary paediatric GI unit experiences' of acute upper GI bleeding demonstrates that a large proportion of centres do not have protocols in place in their own centre or referring units, with most centres performing fewer than 20 therapeutic endoscopic procedures for upper GI bleeding annually. The majority of centres have a small number of consultants competent in upper GI haemorrhage management with limited opportunities for training. There is also limited development of managed clinical networks that would allow more ready access to expert endoscopy provision. Disclosure of Interest: None Declared.